2007
DOI: 10.1016/j.cell.2007.03.026
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Piwi and piRNAs in Germ Cell Maintenance and Transposon Silencing in Zebrafish

Abstract: Piwi proteins specify an animal-specific subclass of the Argonaute family that, in vertebrates, is specifically expressed in germ cells. We demonstrate that zebrafish Piwi (Ziwi) is expressed in both the male and the female gonad and is a component of a germline-specifying structure called nuage. Loss of Ziwi function results in a progressive loss of germ cells due to apoptosis during larval development. In animals that have reduced Ziwi function, germ cells are maintained but display abnormal levels of apopto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
992
3
16

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 1,026 publications
(1,048 citation statements)
references
References 53 publications
37
992
3
16
Order By: Relevance
“…Proteins with Piwi domains have been described as components of ribonucleoprotein complexes that act in the microRNA/ RNA interference pathway of gene silencing (Fetzer et al, 2002, Lingel et al, 2005. Recently, it was shown that the Piwi gene family are associated with a new class of small RNAs socalled 'piwi-interacting RNAs' (piRNAs) in mammalian spermatogenesis (Hall et al, 2005, Houwing et al, 2007, Hutvagner et al, 2008, Peters et al, 2007, which is one of gene expressing regulatory small non-coding RNAs (ncRNAs). Small ncRNAs are naturally conserved regulators of gene expression described in almost all eukaryotic species including humans (Elbashir et al, 2001, Meister et al, 2004, Sana et al, 2012.…”
Section: Discussionmentioning
confidence: 99%
“…Proteins with Piwi domains have been described as components of ribonucleoprotein complexes that act in the microRNA/ RNA interference pathway of gene silencing (Fetzer et al, 2002, Lingel et al, 2005. Recently, it was shown that the Piwi gene family are associated with a new class of small RNAs socalled 'piwi-interacting RNAs' (piRNAs) in mammalian spermatogenesis (Hall et al, 2005, Houwing et al, 2007, Hutvagner et al, 2008, Peters et al, 2007, which is one of gene expressing regulatory small non-coding RNAs (ncRNAs). Small ncRNAs are naturally conserved regulators of gene expression described in almost all eukaryotic species including humans (Elbashir et al, 2001, Meister et al, 2004, Sana et al, 2012.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Notably, various mRNA degradative enzymes are found in mRNP granules besides P-bodies, such as Xrn1 in stress granules 11 and Drosophila/mouse spermatid nuage, 65 Dcp1/ Dcp2 in various germ granules, [66][67][68] and several Argonaute proteins with endonuclease activity in stress granules, 69 and various germ granules. [70][71][72][73] Whether mRNA degradation occurs in mRNP granules besides P-bodies remains poorly studied.…”
Section: Mrnp Granules Assemble Via Common Mechanismsmentioning
confidence: 99%
“…We deemed this analysis necessary since this modification is thought to maintain the stability of piRNAs [23][24][25][26][27][28]. In addition, the PIWI proteins in Drosophila interact with the piRNA methyltransferase, which in turn may be necessary for the methylation of piRNAs [27].…”
Section: Mili-associated Pirnas Are Upregulated But Not Downregulatedmentioning
confidence: 99%